A nonstructural protein encoded by a rice reovirus induces an incomplete autophagy to promote viral spread in insect vectors - Jia, Dongsheng; Liang, Qifu; Liu, Huan; Li, Guangjun; Zhang, Xiaofeng; Chen, Qian; Wang, Aiming; Wei, Taiyun (PLoS pathogens, 2022)
Viruses can hijack autophagosomes as the nonlytic release vehicles in cultured host cells. However, how autophagosome-mediated viral spread occurs in infected host tissues or organs in vivo remains poorly understood. Here, we report that an important rice reovirus, rice gall dwarf virus (RGDV) hijacks autophagosomes to traverse multiple insect membrane barriers in the midgut and salivary gland of leafhopper vector to enhance viral spread. Such virus-containing double-membraned autophagosomes are prevented from degradation, resulting in increased viral propagation. Mechanistically, viral nonstructural protein Pns11 induces autophagy and embeds itself in the autophagosome membranes. The autophagy-related protein 5 (ATG5)-ATG12 conjugation is essential for initial autophagosome membrane biogenesis. RGDV Pns11 specifically interacts with ATG5, both in vitro and in vivo . Silencing of ATG5 or Pns11 expression suppresses ATG8 lipidation, autophagosome formation, and efficient viral propagation. Thus, Pns11 could directly recruit ATG5-ATG12 conjugation to induce the formation of autophagosomes, facilitating viral spread within the insect bodies. Furthermore, Pns11 potentially blocks autophagosome degradation by directly targeting and mediating the reduced expression of N-glycosylated Lamp1 on lysosomal membranes. Taken together, these results highlight how RGDV remodels autophagosomes to benefit viral propagation in its insect vector.